2000
DOI: 10.1016/s1074-7613(00)80163-6
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Some Antigens by the Standard Proteasome but Not by the Immunoproteasome Results in Poor Presentation by Dendritic Cells

Abstract: By stimulating human lymphocytes with an autologous renal carcinoma, we obtained CTL recognizing an antigen derived from a novel, ubiquitous protein. The CTL failed to lyse autologous EBV-transformed B cells, even though the latter express the protein. This is due to the presence in these cells of immunoproteasomes, which, unlike standard proteasomes, cannot produce the antigenic peptide. We show that dendritic cells also carry immunoproteasomes and fail to present this antigen. This may explain why the releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
309
1
6

Year Published

2001
2001
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 373 publications
(332 citation statements)
references
References 49 publications
16
309
1
6
Order By: Relevance
“…Clonal analysis of MART1-specific CTLs has shown that MART1/T-cell receptor interactions are tightly restricted to HLA-A2, 37 and a recent study found that mature human MoDCs do not efficiently process and present the MART1 [27][28][29][30][31][32][33][34][35] epitope from whole MART1 due to the presence of the immunoproteasome, 38 suggesting that delivery of some whole proteins, including MART1, may not be an effective method of antigen delivery to DCs. Immature DCs express both the standard proteasome and immunoproteasomes.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal analysis of MART1-specific CTLs has shown that MART1/T-cell receptor interactions are tightly restricted to HLA-A2, 37 and a recent study found that mature human MoDCs do not efficiently process and present the MART1 [27][28][29][30][31][32][33][34][35] epitope from whole MART1 due to the presence of the immunoproteasome, 38 suggesting that delivery of some whole proteins, including MART1, may not be an effective method of antigen delivery to DCs. Immature DCs express both the standard proteasome and immunoproteasomes.…”
Section: Discussionmentioning
confidence: 99%
“…During an antiviral or antibacterial immune response, immunoproteasomes largely replace constitutive proteasomes (Khan et al 2001). This replacement has a positive effect on MHC class I restricted antigen presentation, as has been demonstrated in several systems (see, for example, Kuckelkorn et al 1995;Ehring et al 1996;Morel et al 2000;Sijts et al 2000b;Van Hall et al 2000;Chen et al 2001;Khan et al 2001;Schultz et al 2002). The immunoproteasomes are not absolutely necessary to generate immunogenic epitopes, but immunodominant epitopes are mainly generated by the immunoproteasomes .…”
Section: Introductionmentioning
confidence: 92%
“…Consequently, the immunoproteasome should generate more MHC ligands. However, it appears that the induction of the immunoproteasome can also abrogate the presentation of antigens (Morel et al 2000) (for a review on this subject see Van den Eynde and Morel (2001). Some epitopes are generated by both proteasomes (see, for example, Sun et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we hypothesized that different machinery for Ag processing resulted in these discrepancies in generation of the LMP1 epitope. A0206-293T cells predominantly express standard proteasomes while in CD40-B cells and LCL immunoproteasomes are dominant [27,28]. Standard proteasomes play a critical role in the Ag processing pathway, and exposure of cells to IFN-c during immune responses alters the proteasome activity qualitatively and quantitatively by induction of newly synthesized immunoproteasome b subunits, such as low-molecular-weight protein (ip-LMP) 2 and ip-LMP7 [29], assembling immunoproterasomes.…”
Section: Requirement Of the Immunoproteasome Subunit Ip-lmp7 For Genementioning
confidence: 99%